Kontribusi Durasi Merokok sebagai Penyebab Terjadinya Karies Gigi pada Penghuni Panti Sosial - Pindobilowo; Dwi Ariani; Margaretha Herawati; Nazwa Akhvina (Universitas Sam Ratulangi, 2023)
Abstract: Smoking duration can have a number of detrimental effects on oral health including tooth loss, periodontal disease, oral soft tissue changes, excessive tooth wear, halitosis, implant failure, oropharyngeal cancer, and dental caries. This study aimd to analyze the relationship between smoking duration and the occurrence of dental caries among residents of social care institutions. This was an observational and analytical study with a cross-sectional design. Samples were 100 residents of Panti Sosial Bina Insan Bangun Daya 1, Kedoya Jakarta Barat, taken by purposive sampling technique. Data were collected by examining dental caries experience with the DMF-T index to obtain the status of dental caries and filling out a questionnaire to obtain the frequency of smoking duration. The Spearman correlation test showed a p-value of 0.436 with a coefficient of r = 0.079 for the relationship between smoking duration and the occurrence of dental caries. In conclusion, there is no relationship between duration of smoking and the occurrence of dental caries in residents of social care institutions. However, the prevalence of caries experience for those residents reaches 96% with an average DMF-T index of 4.8 which is categorized as high according to WHO. Keywords: dental caries; duration of smoking; residents of social care institutions; index DMF-T Abstrak: Durasi merokok dapat memiliki sejumlah efek merugikan pada kesehatan mulut, antara lain kehilangan gigi, penyakit periodontal, perubahan jaringan lunak oral, keausan gigi yang berlebihan, halitosis, kegagalan implan, kanker orofaringeal, dan karies gigi. Penelitian ini bertujuan untuk menganalisis hubungan antara durasi merokok dengan terjadinya karies gigi di panti sosial. Penelitian ini menggunakan metode observasional analitik dengan desain potong lintang. Sampel penelitian berjumlah 100 orang penghuni panti sosial Bina Insan Bangun Daya 1, Kedoya Jakarta Barat, yang diambil dengan teknik purposive sampling. Pengambilan data melalui pemeriksaan pengalaman karies gigi dengan indeks DMF-T untuk melihat status karies gigi dan pengisian kuesioner untuk melihat frekuensi durasi merokok. Hasil uji korelasi Spearman terhadap hubungan antara durasi merokok dengan terjadinya karies gigi memperoleh nilai p=0,436 dengan koefisien r = 0,079. Simpulan penelitian ini ialah tidak terdapat hubungan antara durasi merokok dengan terjadinya karies gigi pada penghuni panti sosial. Prevalensi pengalaman karies penghuni panti panti sosial mencapai 96% dengan rerata indeks DMF-T sebesar 4,8 yang tergolong tinggi menurut WHO. Kata kunci: karies gigi; durasi merokok; penghuni panti sosial; indeks DMF-T